Post-Fire Succession and Montezuma Quail in a Semi-Desert Grassland of Southeast Arizona - Pedro M. Chavarria; Nova J. Silvy; Roel R. Lopez; Christine Hass; Linda Kennedy (National Quail Symposium Proceedings, 2017)
A 1,011.7-ha wildfire occurred in southeast Arizona in May 2009 and provided an opportunity to evaluate pre- and post-fire abundance of and habitat use by Montezuma quail (Cyrtonyx montezumae) through use of flush surveys and radiotelemetry. We evaluated movements of radio-marked quail from 2 months prior to the burn to 12 months post-burn. We observed strong site fidelity with coveys persisting in small patches of unburned areas and micro-topography, despite extensive reduction in cover in the surrounding landscape. We documented 46.7% reduction in abundance using flush counts within the first 2 weeks post-fire, and 66.7% reduction within 3 weeks post-fire. We also documented roosting within a fire-affected area and successful nesting by Montezuma quail a few months following a wildfire.
Keywords: Appleton-Whittell Research Ranch; Cyrtonyx montezumae; dog survey; flush count; Montezuma quail; National Audubon Society; nesting; post-fire succession; radiotelemetry; roosting; wildfire